Feasibility Study and Aspen Plus Simulation for the Manufacture of Virgin Polylactic Acid (PLA) Resins via Ring-Opening Polymerization: A Pilot Plant Proposal in the Philippines - Tristan Roy L Panaligan; Jesuniño Aquino; Dane Kimberly D Collado; Jan Paolo M Maceren; Gio Andrey M Torres (Chemical Engineering Transactions)
Globally, plastic pollution has become a major concern environmentally due to its affinity to degrade for generations. The Philippines is known to be the 3rd ranking contributor to plastic pollution in the world as around 2.7 Mt of plastics are generated yearly. A large portion of these non-biodegradable plastics enter the oceans which negatively impacts marine life and even the livelihood of vulnerable coastal communities. From this perspective, biodegradable plastics have been introduced to remedy the problem, and polylactic acid (PLA) has been known to be both biobased and biodegradable, with good mechanical qualities, biocompatibility, low toxicity, and high compostability. PLA is produced by using lactic acid as the main raw material in the process which involves 3 stages: pre-polymerization, lactide formation, and ring-opening polymerization (ROP). This study seeks to design, simulate, and establish a polylactic acid production plant in the Philippines and evaluate its economic feasibility. Using Aspen Plus v11 as a plant design simulation software, the final product has a desirable weight-average molecular weight of 261,364.22 g/mol in the form of pellets for further use. From the results of the feasibility study of this plant design, the simulation can produce about 30,000 t of PLA which will be exported to China, South Korea, Italy, and Belgium. Financial calculations for this pilot plant proposal have been proven to provide a high return of investment at 28.15 % with a short payback period of 5 y.